Costs and Benefits of Joining the Euro Area: The Case of Croatia - Alina RADU (GINGHINA); Andreea-Georgiana MINCU; Alexandru-Marian SOACATE; Corneliu Florin PARASCHIV; Daniel LAZAR (Communications of International Proceedings, 2022)
After World War II, Croatia became a part of the Federal Republic of Yugoslavia, along with Serbia, Slovenia, Bosnia and Hertegovina and North Macedonia. Even if it was considered a socialist country, Yugoslavian economy had features that resembles a capitalist economy (Losoncz et al., 2021) such as dependency of an integration with world markets, a banking system similar with the one from capitalist countries, meaning borrowing from the banks abroad and attracting deposit in foreign currencies in order to finance domestic companies and households, the existence of unemployment which is atypical for socialist countries. Croatia became independent in 1991 during the Yugoslavian wars. Croatia introduced its own currency in 1994 (kuna) and became a member of the EU in 2013. With a population of 4 million people, Croatia’s GDP represents 0.4% of total EU’s GDP. GDP is divided between the following sectors: 70% for services, 20% for industry, 8% for constructions and 2% for agriculture. In order to assess if Croatia should join the euro area, we are going to analyse potential costs and benefits, according to Optimum Currency Area (OCA) Theory.
Keywords: optimum currency area; monetary union; symmetric and asymmetric shocks